2009
DOI: 10.15288/jsad.2009.70.426
|View full text |Cite
|
Sign up to set email alerts
|

Some Medical Inpatients With Unhealthy Alcohol Use May Benefit From Brief Intervention

Abstract: ABSTRACT. Objective: Studies of alcohol brief intervention for medical inpatients have mixed results. We explored potential moderators of the effectiveness of brief intervention for unhealthy alcohol use among medical inpatients. Method: This is a secondary analysis of a randomized controlled trial of brief motivational counseling among 341 urban-hospital medical inpatients (99 women) with unhealthy alcohol use. Self-reported main outcomes were receipt of alcohol treatment by 3 months in subjects with dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…In this study, the sample differed strongly from those in the other RCTs with a high percentage (37.9% in BI, 35.2% in control group), screening positive for alcohol dependence. BIs for alcohol-dependent patients have been found to be not as effective as for non-dependents [66][67][68] .…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the sample differed strongly from those in the other RCTs with a high percentage (37.9% in BI, 35.2% in control group), screening positive for alcohol dependence. BIs for alcohol-dependent patients have been found to be not as effective as for non-dependents [66][67][68] .…”
Section: Discussionmentioning
confidence: 98%
“…However, while the efficacy of brief interventions in outpatient settings for alcohol is fairly well-established (43), the data in support of inpatient brief interventions are far less clear (44)(45)(46)(47)(48)(49). While two noteworthy systematic reviews found the evidence in support of inpatient brief interventions to be inconclusive (50,51) a recent publication from the federally funded SBIRT (Screening, Brief Intervention, Referral and Treatment) service program, which included the screening of over 450,000 patients from various healthcare settings, including inpatients, concluded that SBIRT is effective in reducing alcohol and drug use by as much as 67.7% after a 6-month follow-up of patients exhibiting at-risk illicit drug use at baseline (52).…”
Section: Discussionmentioning
confidence: 99%
“…This high rate of alcohol dependence may explain the lack of benefit in the overall population. In support of this hypothesis, a secondary analysis of this randomized controlled trial reported that brief interventions did reduce alcohol consumption in general medicine patients with non-dependent risky alcohol use (Saitz et al, 2009). …”
Section: Introductionmentioning
confidence: 93%